2021
DOI: 10.1080/07853890.2021.1999492
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of serum VEGF and sFlt-1 in pernicious placenta previa

Abstract: This study was designed to explore the expression and the diagnostic value of vascular endothelial growth factor (VEGF) and soluble fms-like tyrosine kinase-1 (sFlt-1) in pernicious placenta previa (PPP) combined placental accreta/increta. A total of 140 PPP patients were enrolled and divided into two groups: 56 patients with placenta accreta/increta (PA group), and 84 patients without placenta accreta/increta (non-PA group). In the same period, 46 pregnant women without PPP who had undergone caesarean section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…As a result of electrophoresis performed in placenta previa, VEGF level increased. 25,47 It has been reported that VEGF, which increases in response to placental hypoxia, is not functional during the pathogenesis of preeclampsia. Moreover, since the ligand-receptor binding is impaired, the amount of free VEGF in the preeclamptic placenta increases, impairing vascular function as a result of endothelial cell damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of electrophoresis performed in placenta previa, VEGF level increased. 25,47 It has been reported that VEGF, which increases in response to placental hypoxia, is not functional during the pathogenesis of preeclampsia. Moreover, since the ligand-receptor binding is impaired, the amount of free VEGF in the preeclamptic placenta increases, impairing vascular function as a result of endothelial cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…24 They suggested that VEGF and soluble fms-like tyrosine kinase-1 levels are important for diagnosing placenta previa and can be considered additional parameters to differentiate between placenta accreta and increta. 25 Moreover, the increase in the expression of high mobility group box protein 1 in the placenta may be related to the pathogenesis of placenta previa by regulating the expression of the proangiogenic factor VEGF. 26 In another study, VEGF and leptin levels in 2 nd -trimester amniotic fluid samples taken between 16 and 20 weeks of pregnancy were compared with a control group at 37 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Since VEGF cannot diffuse across biological membranes after binding to circulating sFlt-1, it cannot conduct signaling. 31 sFlt-1 was significantly increased in the preeclamptic placenta at 11 weeks of gestation, with increased expression beginning 5 weeks before the onset of clinical symptoms. 32 Supernatant analysis of placental villus explant in preeclampsia showed a 4-fold increase in sFlt-1 levels compared with normal pregnancy.…”
Section: Placental Growth Factor (Plgf)mentioning
confidence: 95%
“…Since VEGF cannot diffuse across biological membranes after binding to circulating sFlt-1, it cannot conduct signaling . sFlt-1 was significantly increased in the preeclamptic placenta at 11 weeks of gestation, with increased expression beginning 5 weeks before the onset of clinical symptoms .…”
Section: Placental Therapeutic Targetsmentioning
confidence: 99%
“…Serum VEGF was able to predict the need for peripartum hysterectomy by plotting RUC curves (AUC = 0.698, 95% CI 0.564–0.832, LR+2.4, LR−0.3, p = 0.004). This phenomenon provides a clear advantage for clinical application ( 16 18 ). However, due to the study's sample sizes and limited relevant reports, these remain controversial conclusions.…”
Section: Biomarkersmentioning
confidence: 99%